The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1002/hpm.2656
|View full text |Cite
|
Sign up to set email alerts
|

Hospital nurse shift length, patient‐centered care, and the perceived quality and patient safety

Abstract: Patient-centered care mitigates the effect of the shift length on the care outcomes. The study provides an input for the policymakers that patient-centered care and restructuring duty hours are important to provide high-quality patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 34 publications
3
42
0
2
Order By: Relevance
“…There is substantial evidence to suggest the possibility of the association of fatigue and shorter sleep with long working hours, which can lead to loss of concentration and perceived quality of care and PS [13]. A recent study on the effect of hospital nurses’ shift lengths on the perceived quality and PS [35] reported that longer working hours were negatively associated with care quality and safety. More prospective studies are needed to identify the mechanism linking long working hours and perceived or actual PS activities.…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial evidence to suggest the possibility of the association of fatigue and shorter sleep with long working hours, which can lead to loss of concentration and perceived quality of care and PS [13]. A recent study on the effect of hospital nurses’ shift lengths on the perceived quality and PS [35] reported that longer working hours were negatively associated with care quality and safety. More prospective studies are needed to identify the mechanism linking long working hours and perceived or actual PS activities.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, patient and family complaints were substantial. Therefore, several predictors required to be included in the future researches and to be considered by the hospitals' policy makers, such as; staffing, nurse work environment, and patient‐centered care; in order to optimize patient safety and overcome the increased medical and legal complaints in Malaysia. Delivering to the patient proper nutrition, treatment, communication and education help to prevent adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-centred care has a set of attributes, including respect, wholeness, empowerment, collaboration, coordination, effective communication and personalized care (Lor et al, 2016). The approach of patient-centred care is significant for the delivery of high-quality care (Jarrar, Minai, Al-Bsheish, Meri, & Jaber, 2019). It leads to patient satisfaction and effective treatments and reduces the number of emergency department visits, inpatient days and diagnostic tests (Delaney, 2018;Kullberg, Sharp, Johansson, Brandberg, & Bergenmar, 2019).…”
Section: Backg Rou N Dmentioning
confidence: 99%